A study into the links between mortgage financing and economic development in Africa. Issue 1 (7th March 2016) - Asabere, Paul K.; McGowan Jr., Carl B; Lee, Sang Mook
Abstract : Purpose: – The purpose of this paper is to explore the link between mortgage financing and economic development for African countries, as there is a gap in the literature regarding this topic. The development of mortgage markets is important for the overall development of a country. Policymakers and international institutions like the World Bank have been promoting the expansion of Africa's nascent mortgage markets as a logical stimulus to economic growth and development. Specifically, the authors analyze the link between the size of the mortgage market and the gross national income (GNI) per capita for African countries. They found a significant positive correlation between the size of the mortgage market and GNI per capita. A plausible interpretation is that mortgage financing can induce growth and development. Design/methodology/approach: – The authors examine the relationship between mortgage financing and GNI per capita for African countries using the hedonic framework. Findings: – The authors found a significant positive correlation between the size of the mortgage market and the level of GNI per capita, as hypothesized for this study. Practical implications: – An economically plausible interpretation is that the availability of mortgage financing leads to a more efficient financial system, which, in turn, produces growth and development. Social implications: – These findings provide empirical support for the need to pay greater attention to further development and expansion of the emergent mortgage markets of African economies. Originality/value: – There is a gap in the empirical literature regarding this topic with reference to the link between mortgage financing and economic development for African countries.